Correlation between creativity and career choice for senior and vocational high school students in the new normal era - Ernawati, Renatha; Deliviana, Evi; Wigunawati, Eustalia (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
The Demographic Institute of the University of Indonesia conducted a survey in 2015 and noted the difference between education and employment was 53.33%, the difference between occupational qualifications and educational background was 60.52%. Another fact in the study, 63% of Indonesians work not in accordance with their field of science. This study aims to determine the relationship between creativity and students' career choices. Quantitative research method with final correlation design. The object is high school and vocational high school and the subject is 453 students in Jakarta, Depok, Tangerang, and consists of 278 girls and 175 boys. Data collection techniques using instruments. Data analysis using JASP statistical method version 0.16. The results showed that the career choice variables were mostly in the medium category, namely women (60, 80%) and men (57, 71%). Likewise for the creativity variable, mostly in the medium category, namely women (56, 11%) and men (51, 42%). The results also showed that career choice and creativity were highly correlated (p<0.001). It is also known that the Creativity variable can explain the variation in the Career Choice variable by 11.56%. Vice versa, the Career Choice variable can explain variations in Creativity. Based on this value, it can also be explained that the Creativity variable contributes 11.56% to the Career Choice variable.